PENERAPAN ROLE PLAYING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPS KELAS V - Sulistyorini, Endah; Kristin, Firosalia (Jurnal Pendidikan Dasar, 2017)
Abstrack : The background of this research students' low motivation with an average of57.95 and learning outcomes of 13 students (65%) under the KKM (â‰¥65). The purpose of thisstudy to increase motivation and student learning outcomes using model role playing. Thistype of research is a classroom action research with two cycles beginning stages of planning,implementation, observation and reflection. Questionnaire to collect data motivation to learn,about the test, the observation sheet attitudes and skills for student learning outcomes. Datausing descriptive analysis techniques. Motivation in the first cycle "Good" (80%), the secondcycle of "Very Good" (75%). The results of the cognitive aspects of student learning cycle I"Good" score completeness 50%, the second cycle of the category "Good" score of 80%completeness. Psychomotor first cycle an average of 67.5 (enough), the second cycle anaverage of 77.2 (enough). Affective aspects of the first cycle an average of 61.4 (enough), thesecond cycle an average of 67.6 (enough). Thus the suggested role playing learning modelcan be used as one way to increase student motivation and learning outcomes. Keywords: role playing, learning motivation, learning outcomes Abstrak : Penelitian ini dilatar belakangi oleh rendahnya motivasi belajar siswa dengan ratarata 57,95 dan hasil belajar 13 siswa (65%) dibawah KKM (â‰¥65). Tujuan penelitian inimeningkatkan motivasi dan hasil belajar siswa menggunakan model pembelajaran role playing. Jenis penelitian ini adalah Penelitian Tindakan Kelas (PTK) dengan dua siklusdiawali tahap perencanaan, pelaksanaan, pengamatan (observasi), dan refleksi. Angket untukmengumpulkan data motivasi belajar, sedangakn soal tes, lembar observasi sikap danketerampilan untuk hasil belajar siswa. Data menggunakan teknik analisis deskriptif. Motivasipada siklus I â€œBaikâ€ (80%), siklus II â€œSangat Baikâ€ (75%). Hasil belajar siswa aspek kognitifsiklus I â€œBaikâ€ nilai ketuntasan 50%, siklus II kategori â€œBaikâ€ nilai ketuntasan 80%. Aspekpsikomotorik siklus I rata-rata 67,5 (cukup), siklus II rata-rata 77,2 (cukup). Aspek afektifsiklus I rata-rata 61,4 (cukup), siklus II rata-rata 67,6 (cukup). Dengan demikian disarankanmodel pembelajaran role playing dapat digunakan sebagai salah satu cara untukmeningkatkan motivasi dan hasil belajar siswa. Kata kunci : role playing, motivasi belajar, hasil belajar